Environmental impact assessment of the potability of water from bore-hole, hand dug well and stream at Itagunmodi gold deposits Southwestern, Nigeria using FORTRAN algorithm for monitoring leachates and interpreting physicochemical data of contaminants in groundwater (2015)
This study determined the quality of surface and underground water in Itagunmodi in Nigeria. Physicochemical analysis of water samples collected within gold mining area and the water consumed in the town was carried out to determine their hygienic conditions. The major objective of this study was assessment degree of groundwater pollution around the mining sites and the available water consumed in the town. Four major sources of water were analyzed. Several physical and chemical parameters were tested in roundwater, these include pH, total solids (TS), total dissolved solids (TDS), conductivity, total alkalinity, total hardness (TH), chloride (Cl-1), sulphur (S), heavy metals (Pb, Zn, Cu), major cation (Mg). The results show that the parameters are within the standard acceptable levels which are required for drinking water adapted from World Health Organization. The pH of the samples was suitable for drinking according to the World Health Organization standard. For a safe drinking water, the pH should be between 6.5 and 8.5); it can be said that the water quality of the samples are fairly good based on the monitored elements and physicochemical characteristics.